2015
DOI: 10.1002/ece3.1775
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of male insemination success in the mosquitofish (Gambusia holbrooki)

Abstract: Identifying targets of selection is key to understanding the evolution of sexually selected behavioral and morphological traits. Many animals have coercive mating, yet little is known about whether and how mate choice operates when these are the dominant mating tactic. Here, we use multivariate selection analysis to examine the direction and shape of selection on male insemination success in the mosquitofish (Gambusia holbrooki). We found direct selection on only one of five measured traits, but correlational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 67 publications
4
41
0
Order By: Relevance
“…We measured gonopodium length, which affects female mate choice in some poeciliids and has been implicated as a potentially important trait affecting sperm transfer [109–112]. Unexpectedly, we found that small and medium-sized males on a restricted diet early in life had a longer gonopodium, corrected for body size, than those on a regular diet [60, 113]. The fitness consequences of this change in allometry are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…We measured gonopodium length, which affects female mate choice in some poeciliids and has been implicated as a potentially important trait affecting sperm transfer [109–112]. Unexpectedly, we found that small and medium-sized males on a restricted diet early in life had a longer gonopodium, corrected for body size, than those on a regular diet [60, 113]. The fitness consequences of this change in allometry are unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 196 sons (58 Lc, 67 Sc, 10 La, 19 Sa, 21 Li and 21 Si) were tested to measure their reproductive performance. We measured seven traits previously linked to male reproductive success (e.g., Head et al , ; Head et al , ): (a) time to maturity, (b) body size at maturity, (c) relative gonopodium length, (d) attractiveness to females, (e) sexual behaviour, (f) sperm number and (g) sperm velocity.…”
Section: Methodsmentioning
confidence: 99%
“…In total,196 sons (58 Lc,67 Sc,10 La,19 Sa,21 Li and 21 Si) were tested to measure their reproductive performance. We measured seven traits previously linked to male reproductive success (e.g., Head et al, 2017;Head et al, 2015): 21-23 mm in size, which is the modal range in the study population (Kahn et al, 2013). The two-choice tank had three compartments: a central one (49 × 20 × 22 cm) for the test female, and two end sections for males (each 7 × 20 × 22 cm).…”
Section: Female Immune Responsementioning
confidence: 99%
See 1 more Smart Citation
“…In such systems females can exert choice by varying the extent to which they resist mating attempts, or by simply spending more time in proximity to some males versus others [34–36]. Indeed, evidence thus far suggests that females play an important role in male choice in both displaying and in coercive systems [37]. In both cases a key indicator is which males the females choose to associate with.…”
Section: Introductionmentioning
confidence: 99%